Static and Dynamic Indicators of Minority Threat in Sentencing Outcomes: A Multi-Level Analysis - Caravelis, Cyndy (Journal of quantitative criminology, 2011)
Designation as a “Habitual Offender” is an enhanced form of punishment which unlike, “Three Strikes” or “10-20-Life,” is entirely discretionary. We use Hierarchical Generalized Linear Modeling to assess the direct effects of race and Latino ethnicity on the designation of Habitual Offenders as well as the effect of both static and dynamic indicators of racial and ethnic threat on those outcomes. Our data include 26,740 adults sentenced to prison in Florida between 2002 and 2004 who were statutorily eligible to be sentenced as Habitual. The odds of receiving this designation are significantly increased for black and Latino defendants as compared to whites, though race and ethnicity effects vary substantially by crime type, being strongest for drug offenses and negligible for violent crimes. Static measures of group level threat (% black and % Latino) have no cross-level effect on sentencing by race or Latino ethnicity. However, increasing black population over time increases the odds of being sentenced as Habitual for both black and Latino defendants. Increasing Latino population increases the odds of Habitual Offender sentencing for Latinos, but decreases it for blacks. The prospect of engaging dynamic as opposed to static measures of threat in future criminal justice and other social control research is discussed.